Spectroscopic Methods and Analyses NMR, Mass Spectrometry, and Metalloprotein Techniques - Jones, Christopher;Ed. Mulloy, Barbara;Ed (Methods in molecular biology (Clifton, N.J.), v. 17., 1993)
Although spectroscopic methods are of great use to biological scientists, many researchers lack a specialist's knowledge of these techniques. Spectroscopic Methods and Analyses provides hands-on information on these valuable research tools, emphasizing practical aspects, such as amounts and purity of required samples, limitations and advantages of the technique, and interpretation of the results, thus enabling every molecular biologist-either independently or with the help of a specialist-to evaluate the usefulness of a technique, to plan an original program, and to gain a realistic idea of the resources needed. An indispensable guide for all biochemists, cell and molecular biologists, pharmacologists, immunologists, pathologists, and neuroscientists.